Maternal prenatal intake of one-carbon metabolism nutrients and risk of childhood leukemia - Singer, Amanda W. (Cancer Causes Control, 2016)
PURPOSE: Folate, vitamins B12 and B6, riboflavin, and methionine are critical nutrients for the one-carbon metabolism cycle involved in DNA synthesis and epigenetic processes. We examined the association between maternal intake of these nutrients before pregnancy and risk of childhood acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) in a matched case-control study. METHODS: Maternal dietary intake and vitamin supplement use in the year before pregnancy was assessed by food frequency questionnaire for 681 ALL cases, 103 AML cases, and 1,076 controls. Principal components analysis was used to construct a variable representing combined nutrient intake, and conditional logistic regression estimated the odds ratio (OR) and 95% confidence interval (CI) for the association of ALL and AML with the principal component and each nutrient. RESULTS: Higher maternal intake of one-carbon metabolism nutrients from food and supplements combined was associated with reduced risk of ALL (OR for one-unit change in the principal component=0.91, CI 0.84–0.99) and possibly AML (OR for the principal component=0.83, CI 0.66–1.04). When analyzed separately, intake of supplements high in these nutrients was associated with a reduced risk of ALL in children of Hispanic women only. CONCLUSIONS: In conclusion, these data suggest that higher maternal intake of one-carbon metabolism nutrients may reduce risk of childhood leukemia.